THE TERTIARISATION OF ECONOMY OF THE REGIONAL SOCIALGEOSYSTEMS OF UKRAINE - Корнус, Анатолій (Human Geography Journal, 2016)
The article describes the level of tertiarisation of economy of the regional socialgeosystems of Ukraine. The study was conducted on the following parameters reflecting the level of development of services: the share of exports in total exports of services, the employment structure, and the structure of gross value added. Particular attention is paid to the development of knowledge-intensive and business services, as well as on the amount of research and development activities in the regions of Ukraine. Achieved the ranking of regional socialgeosystems of Ukraine by the level of tertiarisation of the their economies.